Intratumor lactate levels reflect HER2 addiction status in HER2‐positive breast cancer. Issue 2 (21st August 2018) - Castagnoli, Lorenzo; Iorio, Egidio; Dugo, Matteo; Koschorke, Ada; Faraci, Simona; Canese, Rossella; Casalini, Patrizia; Nanni, Patrizia; Vernieri, Claudio; Di Nicola, Massimo; Morelli, Daniele; Tagliabue, Elda; et al.
Abstract : Despite different molecular tumor profiles indicate that human epidermal growth factor receptor 2 (HER2) messenger RNA (mRNA) levels mirror HER2 addiction and trastuzumab benefit in HER2‐positive breast cancer (BC), the identification of noninvasive clinical predictors of trastuzumab sensitivity remains an unmet clinical need. In the current study, we investigated whether intratumor lactate levels reflect HER2 addiction and, in turn, trastuzumab susceptibility. Accordingly, the gene expression profiles of transgenic murine BC cell lines expressing the human d16HER2 variant (HER2‐addicted) or human full‐length HER2 (WTHER2; HER2‐nonaddicted) revealed a significant enrichment of glycolysis‐related gene pathways in HER2‐addicted cells. We studied the metabolic content of 22 human HER2‐positive BC by quantitative nuclear magnetic resonance spectroscopy and found that those cases with higher lactate levels were characterized by higher HER2 transcript levels. Moreover, gene expression analyses of HER2‐positive BC samples from a TCGA data set revealed a significant enrichment in glycolysis‐related pathways in high/HER2‐addicted tumors. These data were confirmed by metabolic analyses of human HER2‐positive BC cell lines with high or low HER2 transcript levels, which revealed significantly more active glycolytic metabolism in high HER2 transcript than in low HER2 transcript cells. Overall, our results provide evidence for noninvasive intratumor lactate detection as a potential metabolic biomarker of HER2 addiction and trastuzumab response suggesting the possibility to use in vivo imaging to assess lactate levels and, in turn, select HER2‐positive BC patients who are more likely to benefit from anti‐HER2 treatments. Abstract : The purpose of this study was to identify a reliable, noninvasive, and novel biomarker associated with HER2 addiction that reflects the susceptibility to HER2‐specific therapy. Our results provide experimental and relevant support for the preclinical and clinical association between HER2 addiction/trastuzumab susceptibility and intratumor levels of lactate, a key metabolic player in cancer progression that is upregulated early in the development of malignancies. Through molecular and metabolic analyses, we found a statistically significant association among HER2 transcript levels, intratumor lactate levels and response to therapy, thus paving the way for the utilization of Magnetic Resonance Imaging and Magnetic Resonance Spectroscopy as a powerful and independent tool to better tailor anti‐HER2 therapies and improve the outcomes of all patients with HER2‐positive BC.